Small Bowel Imaging in Managing Crohn's Disease Patients. (14th February 2012) - Albert, Jörg G.
Abstract : The small bowel is essential to sustain alimentation and small bowel Crohn's disease (CD) may severely limit its function. Small bowel imaging is a crucial element in diagnosing small bowel CD, and treatment control with imaging is increasingly used to optimize the patients outcome. Thereby, capsule endoscopy, Balloon-assisted enteroscopy, and Magnetic resonance imaging have become key players to manage CD patients. In this review, role of small bowel imaging is detailed discussed for use in diagnosing and managing Crohn's disease patients.